Islamism in Politics: Integration and Persecution in Egypt - DeGregorio, Christina (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2010)
This paper tries to portray the why in which Islamism reacted to political constellation in the Egyptian context from the time of Anwar Sadat to of Hosni Mubarak. It shows that the Egyptian government from time to time often adopts a harsh policy toward any forms of extremism in the name of Islam. However, persecution led to nothing but the increase of radical Islamism. This occurred because the Islamist movement failed to integrate their ideas in the real political domain. Failure in integration to both political and social life fueled further exclusivism.